INTERNALISASI CINTA TANAH AIR BERBASIS NILAI PANCASILA MELALUI PEMBIASAAN LAGU INDONESIA RAYA DI SD YPWKS V - Novi Nurhayati; Firman Robiansyah; Oki Suprianto (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
The low appreciation of nationalist values ​​among elementary school students shows the need for structured and sustainable habituation strategies. This research aims to analyze the process of internalizing love for the homeland based on Pancasila values ​​through familiarization with the song Indonesia Raya and its implications for the formation of an attitude of love for the homeland of class V students at SD YPWKS V. The research uses a qualitative approach with a case study design. Data sources consist of school principals, fifth grade teachers, and students. Research instruments include observation guidelines, interview guidelines, documentation, and questionnaires. Data collection techniques use non-participatory observation, interviews, documentation and questionnaires. Data analysis uses the Miles and Huberman interactive model through the stages of data reduction, data presentation, and drawing conclusions. Test validity with triangulation. The research results show that internalization takes place through the stages of value transformation, example, and consistent habituation to form discipline, a sense of pride, and an attitude of love for the country. It is recommended that schools maintain program consistency and strengthen the role of teachers as role models in character education.